2010
DOI: 10.1002/fuce.200900114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GDL Structure with an Efficient Approach to the Management of Liquid water in PEM Fuel Cells

Abstract: A model fuel cell with a single transparent straight flow channel and segmented anode was constructed to measure the direct correlation of liquid water movement with the local currents along the flow channel. Water drops emerge through the largest pores of the GDL with the size of the droplets that emerge on the surface determined by the size of the pore and its location under the gas flow channel or under the land. Gravity, surface tension, and the shearing force from the gas flow control the movement of liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
0
28
0
2
Order By: Relevance
“…Many studies have revealed the importance of gravity effect on the performance and water management of PEMFC by changing the orientation of the fuel cell. Kimball et al [28,29] observed the liquid water motion in PEMFC by changing the PEMFC orientation. Different characteristics were observed with different orientations of the flow channels.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the importance of gravity effect on the performance and water management of PEMFC by changing the orientation of the fuel cell. Kimball et al [28,29] observed the liquid water motion in PEMFC by changing the PEMFC orientation. Different characteristics were observed with different orientations of the flow channels.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Kimball et al [37] coupled with the GDL characterization presented here show that the flow of water from the catalyst layer through the GDL is a component of the fuel cell design. Pores may be created in a hydrophobic GDL material that can minimize flooding, improve membrane humidification, and facilitate water removal.…”
Section: Implications For Fuel Cell Designmentioning
confidence: 79%
“…Gerteisen et al experimentally demonstrated that systematically perforating carbon paper with knowledge of the flow channel structure reduces water accumulation and results in increased limiting current densities of 8-22% [36]. Kimball et al [37] created flow directing pores through the GDL. They reported the highest current density was achieved with a vertical flow channel, gas flow down, and the flow directing pore under the rib near the cathode gas inlet.…”
Section: Introductionmentioning
confidence: 99%
“…In comparing the performance of fuel cells in different placement positions of the cathode and anode, they found that liquid water discharge inside the fuel cell with a cathode-upward flow field is superior to that inside the anode-upward flow field. Morin et al [32] analyzed the spectra of liquid content outside the membrane and found that, for a constant current density, the performance of the cell is enhanced for a symmetric configuration when the cathode inlet is placed at the bottom of flow field because of better membrane hydration. Lee et al [34] also presented the impact of gravitational level on cell polarization characteristics and liquid water discharge phenomenon.…”
Section: Introductionmentioning
confidence: 99%